PENATAAN KAWASAN PASCA BENCANA TANAH LONGSOR DI PUNCAK PASS, KECAMATAN CIPANAS, KABUPATEN CIANJUR TANGGAL 28 MARET 2018 - Sri Naryanto, Heru; Prawiradisastra, Firman; Kristijono, Agus; Ganesha, Deliyanti (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2019)
Landslides often occur in Indonesia, including in Puncak which is a tourist area. A landslide disaster occurred at Puncak Pass, Cipanas Sub-district, Cianjur District, West Java on Wednesday, March 28, 2018 at around 08.00 PM. Typology of landslides that occur is a debris slide consisting of debris materials such as soil, rocks and large trees, and form a basin such as the shape of a horseshoe on the former landslide. Landslide occurred on the slope of the road and destroyed the hotel building, the park behind the hotel and pine forest. Many factors that influence the occurrence of landslide in Puncak Pass, from the analysis there are three main factors causing the landslide: the topography of the landslide is very steep, the occurrence of heavy rain for several consecutive days before the occurrence of landslides, and the slope which always disrupted the transport load of vehicles on it. Arrangement of landslide areas is very important to re-arrange the sustainable condition of the area against similar landslide disaster in the future. These arrangements are: handling of landslides during emergency response, determining the location of new road development, water and drainage management, cliff strengthening, land management, potentially affected settlements, and landslide disaster management. Keywords: Landslide, Puncak Pass, debris slide, sustainable safe area arrangement